Environmental Accounting Practices and Corporate Global Performance in an Emerging Market: The Mediating Role of Environmental Disclosure - Hanan Hammami; Mahmoud Zouaoui (Inclusive Society and Sustainability Studies, 2024)
Environmental accounting practices (EAP) serve as a comprehensive system for monitoring and reporting environmental facts, effectively addressing the limitations of traditional accounting. A review of the literature indicates that most studies on EAP have primarily focused on demonstrating their positive impact, particularly on companies’ financial performance. The objective of this study is to empirically examine the relationship between EAP and corporate global performance (CGP), incorporating environmental and commercial dimensions. Drawing on the contractual approach and legitimacy theory, we propose a research model that elucidates the mechanisms through which EAP influences CGP, with a focus on the indirect effect of environmental disclosure on this relationship. The primary contribution of this research lies in the development of a conceptual model that integrates variables suggested in the literature but never tested together. To the best of our knowledge, no prior studies have explored the indirect effects of environmental disclosure on the EAP-CGP relationship. Our findings indicate that EAP has a positive influence on all three dimensions of global performance. The results also demonstrate that environmental disclosure mediates the relationship between EAP and the financial and commercial dimensions of performance.